FINANCIAL KNOWLEDGE DAN GAYA HIDUP DALAM MENGUKUR FINANCIAL BEHAVIOUR GENERASI Z DARI PERSPEKTIF PENGGUNAAN MOBILE PAYMENT - Lestara Permana, Gusi Putu; Adnyani, Ni Putu Mita; Laksmi P, Kadek Wulandari (Universitas Prof.Hazairin,SH Bengkulu, 2023)
This study aims (1) to determine the effect of financial knowledge on the financial behavior of mobile payment users. (2) to determine the effect of lifestyle on the financial behavior of mobile payment users. This research was conducted on a digital payment system, namely mobile payment. The population in this study is Generation Z who use mobile payment services in Denpasar City and the sample in this study is 80 respondents. The data analysis techniques used in this study are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, Simultaneous Significance Test (F-Test) and Partial Test (T-Test) with the help of SPSS software for windows. Result of this research shows (1) financial knowledge has a significant positive effect on the use of mobile payments, (2) lifestyle has a significant positive effect on the use of mobile payments